Stealing the network : how to own the box - Russell, Ryan, 1969- (Cyber-Fiction Ser., 2003)
"Stealing the Network: How to Own the Box" is NOT intended to be a "install, configure, update, troubleshoot, and defend book." It is also NOT another one of the countless Hacker books out there. So, what IS it? It is an edgy, provocative, attack-oriented series of chapters written in a first hand, conversational style. World-renowned network security personalities present a series of 25 to 30 page chapters written from the point of an attacker who is gaining access to a particular system. This book portrays the "street fighting" tactics used to attack networks and systems. Not just another "hacker" book, it plays on "edgy" market success of Steal this Computer Book with first hand, eyewitness accounts A highly provocative expose of advanced security exploits Written by some of the most high profile "White Hats", "Black Hats" and "Gray Hats" Gives readers a "first ever" look inside some of the most notorious network intrusions